Pendampingan dan Pembuatan Pupuk Organik dalam Mengurangi Biaya Pupuk Petani Desa Rowo Gempol - Mohammad Zidan Rafsanjani; Siti Fatimatuzzahro; Wafiq Nur Azizah; Samsul Arifin; Utami Puji Lestari; Mila Hariani; Arif Rachman Putra (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Organic fertilizers contain organic materials such as compost, manure, or other organic waste materials. When organic fertilizers are applied to the soil, they provide an abundant source of nutrients, including nitrogen, phosphorus, and potassium, as well as essential micronutrients. The community service activity program aims to empower farmers with the knowledge and skills to make organic fertilizers from local materials, which not only lower production costs but also improve soil quality and crop yields. The community service activity with the theme